Myocardial Infarction Can Be Safely Excluded by High‐sensitivity Troponin I Testing 3 Hours After Emergency Department Presentation. (27th March 2020) - Peacock, W. Frank; Christenson, Robert; Diercks, Deborah B.; Fromm, Christian; Headden, Gary F.; Hogan, Christopher J.; Kulstad, Erik B.; LoVecchio, Frank; Nowak, Richard M.; Schrock, Jon W.; Singer, Adam J.; Storrow, Alan B.; et al.
Abstract: Background: The accuracy and speed by which acute myocardial infarction (AMI) is excluded are an important determinant of emergency department (ED) length of stay and resource utilization. While high‐sensitivity troponin I (hsTnI) >99th percentile (upper reference level [URL]) represents a "rule‐in" cutpoint, our purpose was to evaluate the ability of the Beckman Coulter hsTnI assay, using various level‐of‐quantification (LoQ) cutpoints, to rule out AMI within 3 hours of ED presentation in suspected acute coronary syndrome (ACS) patients. Methods: This multicenter evaluation enrolled adults with >5 minutes of ACS symptoms and an electrocardiogram obtained per standard care. Exclusions were ST‐segment elevation or chronic hemodialysis. After informed consent was obtained, blood samples were collected in heparin at ED admission (baseline), ≥1 to 3, ≥3 to 6, and ≥6 to 9 hours postadmission. Samples were processed and stored at –20°C within 1 hour and were tested at three independent clinical laboratories on an immunoassay system (DxI 800, Beckman Coulter). Analytic cutpoints were the URL of 17.9 ng/L and two LoQ cutpoints, defined as the 10 and 20% coefficient of variation (5.6 and 2.3 ng/L, respectively). A criterion standard MI diagnosis was adjudicated by an independent endpoint committee, blinded to hsTnI, and using the universal definition of MI. Results: Of 1, 049 patients meeting the entry criteria, and with baseline and 1‐ to 3‐hour hsTnI results, 117 (11.2%) had an adjudicated final diagnosis of AMI. AMI patients were typically older, with more cardiovascular risk factors. Median (IQR) presentation time was 4 (1.6–16.0) hours after symptom onset, although AMI patients presented ~0.5 hour earlier than non‐AMI. Enrollment and first blood draw occurred at a mean of ~1 hour after arrival. To evaluate the assay's rule‐out performance, patients with any hsTnI > URL were considered high risk and were excluded. The remaining population ( n  = 829) was divided into four LoQ relative categories: both hsTnI < LoQ (Lo‐Lo cohort); first hsTnI < LoQ and 2nd > LoQ (Lo‐Hi cohort); first > LoQ and second < LoQ (Hi‐Lo cohort); or both > LoQ (Hi‐Hi cohort). In patients with any hsTnI result <20% CV LoQ (Groups 1–3), n  = 231 (23.9% ruled out), AMI negative predictive value (NPV) was 100% (95% confidence interval [CI] = 98.9% to 100%). In patients with any hsTnI below the 10% LoQ, n  = 611 (58% rule out), AMI NPV was 100% (95% CI = 99.5% to 100%). Of the Hi‐Hi cohort (i.e., no hsTnI below the 10% LoQ, but both < URL), there were four AMI patients, NPV was 98.2% (95% CI = 95.4% to 99.3%), and sensitivity was 96.6. Conclusions: Patients presenting >3 hours after the onset of suspected ACS symptoms, with at least two Beckman Coulter Access hsTnI < URL and at least one of which is below either the 10 or the 20% LoQ, had a 100% NPV for AMI. Two hsTnI values 1 to 3 hours apart with both < URL, but also >LoQ had inadequate sensitivity and NPV.